Virus induced gene silencing confirms oligogenic inheritance of brown stem rot resistance in soybean - McCabe, Chantal E.; Lincoln, Lori M.; O’Rourke, Jamie A.; Graham, Michelle A. (Frontiers in Plant Science, 2024)
Brown stem Stem Rrot (BSR), caused by the soil borne fungal pathogen Phialophora gregata, can reduce soybean yields by as much as 38%. Previous allelism studies identified three Resistant to Brown Stem Rrot genes (Rbs1, Rbs2, and Rbs3), all mapping to large, overlapping regions on soybean chromosome 16. However, recent fine-mapping and genome wide association studies (GWAS) suggest Rbs1, Rbs2, and Rbs3 are alleles of a single Rbs locus. To address this conflict, we characterized the Rbs locus using the Williams82 reference genome (Wm82.a4.v1). We identified 120 Rreceptor Llike Pproteins (RLPs), with hallmarks of disease resistance receptor-like proteins (RLPs), which formed five distinct clusters. We developed virus induced gene silencing (VIGS) constructs to target each of the clusters, hypothesizing that silencing the correct RLP cluster would result in a loss of resistance phenotype. The VIGS constructs were tested against P. gregata resistant genotypes L78-4094 (Rbs1), PI 437833 (Rbs2), or PI 437970 (Rbs3), infected with P. gregata or mock infected. No loss of resistance phenotypes wasere observed. We then developed VIGS constructs targeting two RLP clusters with a single construct. Construct B1a/B2 silenced P. gregata resistance in L78-4094, confirming at least two genes confer Rbs1-mediated resistance to P. gregata. Failure of B1a/B2 to silence resistance in PI 437833 and PI 437970 suggests additional genes confer BSR resistance in these lines. To identify differentially expressed genes (DEGs) responding to silencing, we conducted RNA-seq of leaf, stem and root samples from B1a/B2 and empty vector control plants infected with P. gregata or mock infected. B1a/B2 silencing induced DEGs associated with cell wall biogenesis, lipid oxidation, the unfolded protein response and iron homeostasis and repressed numerous DEGs involved in defense and defense signaling. These findings will improve integration of Rbs resistance into elite germplasm and provide novel insights into fungal disease resistance.